Global remote sensing research trends during 1991–2010: a bibliometric analysis - Zhuang, Yanhua; Liu, Xingjian; Nguyen, Thuminh; He, Qingqing; Hong, Song (Scientometrics, 2013)
According to the articles related to remote sensing of SCI and SSCI databases during 1991–2010, this study evaluated the geographical influence of authors by the new index (geographical impact factor), and revealed the auctorial, institutional, national, and spatiotemporal patterns in remote sensing research. Remote sensing research went up significantly in the past two decades. Imaging science & photographic technology was the important subject category. International Journal of Remote Sensing was the top active journal. All authors were mainly concentrated in North America, Western Europe, and East Asia. Jackson TJ from USDA ARS was the most productive author, Coops NC from University of British Columbia had more high-quality articles, and Running SW from University of Montana carried the greatest geographical influence. The USA was the largest contributor in global remote sensing research with the most single-country and internationally collaborative articles, and the NASA was the most powerful research institute. The international cooperation of remote sensing research increased distinctly. Co-word analysis found the common remote sensing platform and sensors, revealed the widespread adoption of major technologies, and demonstrated keen interest in land cover/land use, vegetation, and climate change. Moreover, the remote sensing research was closely correlated with the satellite development.